What safety can we talk about when all we see is difficulty? The impact of geographic and cultural determinants of unintentional injury in rural and mountainous Mugu, Nepal - Katherine Weatherburn; Divya Parmar; Puspa Raj Pant; Monila Parajuli; Jamie Murdoch (Frontiers in Public Health)
IntroductionUnintentional injuries are a significant health concern in rural Nepal, where geographic isolation and limited healthcare infrastructure exacerbate their impact. In the remote district of Mugu, primary caregivers of children navigate complex physical and social landscapes daily. This study explores how primary caregivers perceive the determinants of injury. By examining the interplay of environmental, social, and infrastructural determinants shaping injury risks, the findings provide insights into the unique challenges of injury in rural settings.MethodsIn 2017, seven focus group discussions were conducted with 56 participants (95% female) in Mugu, Nepal. Using Braun and Clarke's thematic analysis framework, transcripts were analysed inductively, using NVivo 14 to assist with coding and identification of themes.ResultsFive themes were identified; “Precarious environment,” “Limited choices due to life precarity,” “Gendered labour roles,” “Perceived control over injuries,” and “Healthcare access and quality,” with environment and gender underpinning all themes. Unintentional injuries were normalised, and outdoor environmental risks perceived as beyond primary caregivers' control. Conversely, some agency was expressed in home safety practices. Fatalistic beliefs served as coping mechanisms. Barriers to healthcare access led to reliance upon traditional remedies, adversely affecting injury outcomes.DiscussionsEnvironmental, gender and socio-cultural factors shape injury patterns and prevention opportunities in Mugu. Primary caregivers face constrained options for prevention. However, local, municipality level policies which are socio-culturally relevant and tailored to meet caregiver needs, alongside infrastructure improvements, provide an opportunity to mitigate injury risks and also reduce associated socioeconomic impacts.